CONFIRMATION THEORETICAL MODEL OF SUSTAINABLE CONSUMPTION - Elena Escalera-Chávez, Milka; Salguero-Romero, Cynthia; García-Cabrera, Valeria; García-Santillán, Arturo (British Journal of Marketing Studies, 2014)
The organic food and product market is a reality in more than 130 countries, including Mexico. The aim of this research was to identify if sustainable consumption may be explained by three factors: Marketing Strategies, Consumer Behavior and Demographics data. In this study, the test designed by Salgado-Beltrán and Beltrán-Morales (2011) consisting of 10 questions with a Likert scaling was replicated. The statistical technique to test whether the proposed theoretical model fits the data was structural equations due to its potential to further develop the theory. The result show that the hypothetical model fits the data very well, as shown by the CFI (0.970) and RMSEA (0.071) values